Effects of SGLT-2 inhibitors on adipose tissue distribution in patients with type 2 diabetes mellitus: a systematic review and meta-analysis of randomized controlled trials - Xianghong Wang; Niujian Wu; Chuanchuan Sun; Donghua Jin; Hongyun Lu (Diabetology & Metabolic Syndrome, 2023)
Abstract Objective Sodium-glucose cotransporter-2 (SGLT-2) inhibitors therapies were reported to affect adipose tissue distribution. However, the available evidence about the effect of SGLT-2 inhibitor on adipose tissue is contradictory. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the effect of SGLT-2 inhibitors on adipose tissue distribution in patients with type 2 diabetes mellitus (T2DM). Methods RCTs on SGLT-2 inhibitors on adipose distribution affect in patients with T2DM published in full-text journal databases such as PubMed, Embase, Cochrane Library, and ClinicalTrials.gov databases were searched. The fixed or random effect model was used for meta-analysis, the I2 test was used to evaluate the heterogeneity between studies, and the sensitivity analysis and subgroup analysis were used to explore the source of heterogeneity. Funnel chart and Begg’s test were used to estimate publication bias. Results Overall, 18 RCTs involving 1063 subjects were evaluated. Compared with placebo or other hypoglycemic drugs, SGLT-2 inhibitors significantly reduced visceral adipose tissue (standard mean deviation [SMD] = − 1.42, 95% confidence interval [CI] [− 2.02, − 0.82], I2 = 94%, p < 0.0001), subcutaneous adipose tissue (SMD = − 1.21, 95% CI [− 1.99, − 0.42], I2 = 93%, p = 0.003), ectopic liver adipose tissue (SMD = − 0.70, 95% CI [− 1.20, − 0.20], I2 = 73%, p = 0.006). In addition, body weight (mean deviation [MD] = − 2.60, 95% CI [− 3.30, − 1.89], I2 = 95%, p < 0.0001), waist circumference (MD = − 3.65, 95% CI [− 4.10, − 3.21], I2 = 0%, p < 0.0001), and body mass index (BMI) (MD = − 0.81, 95% CI [− 0.91, − 0.71], I2 = 23%, p < 0.0001) were significantly decreased. However, epicardial fat tissue showed an insignificant reduction (SMD = 0.03, 95% CI [− 0.52, 0.58], I2 = 69%, p = 0.71). Subgroup analysis revealed that appropriate treatment duration (16 – 40 weeks) or young patients with nonalcoholic fatty liver disease (NAFLD) and obesity were the decisive factors for SGLT-2 inhibitors to effectively reduce visceral and subcutaneous adipose tissues. Conclusions Our meta-analysis provides evidence that in patients with T2DM, SGLT-2 inhibitors significantly reduce visceral adipose tissue, subcutaneous adipose tissue, and ectopic liver fat, especially in young T2DM patients with NAFLD and high BMI. Appropriate dosing time (16–40 weeks) may have a more significant and stable beneficial effect on VAT and SAT reduction.